A comparison of hamstring musculotendon dynamics during high-speed running before and after a fatigue exercise - Miyazaki, T.; Fujii, N. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to compare the musculotendon dynamics of individual hamstring muscles between before and after a soccer-specific fatigue exercise during the late swing phase of high-speed running. Eight male soccer players performed three sprintings before and after the fatigue exercise. Whole-body kinematic data and ground reaction forces of the support leg were recorded using a three-dimensional motion analysis system and force platform. A three-dimensional musculoskeletal model with 43 Hill-type musculotendon models was used to estimate the musculotendon dynamics. The results of this study showed that there were no significant differences in the peak values of musculotendon force, power, length, and elongation velocity in the hamstring muscles before and after the fatigue exercise.